Boosting catalytic wet-peroxide-oxidation performances of cobalt ferrite by doping with lanthanides for organic pollutants degradation. Issue 1 (February 2021) - Samoila, Petrisor; Cojocaru, Corneliu; Mahu, Elvira; Ignat, Maria; Harabagiu, Valeria
Abstract: Up-to-date no study was reported dealing with cobalt ferrite-based catalysts for wet hydrogen peroxide oxidation (CWPO) of organic pollutants. In this respect, degradation of Rhodamine 6G-(Rh6G) was assessed by cobalt ferrites doped with lanthanum, gadolinium and dysprosium cations, for the first time. The ED-XRF proved the stoichiometry of catalysts. The XRD analysis confirmed the successful accommodation of the bulky rare-earth cations into the spinel matrix. The performance of the cobalt ferrite in CWPO process was categorically improved by doping. Thus, the Rh6G degradation efficiency after only 15 min of catalytic process was enhanced from 35.7% for the undoped cobalt ferrite to 92.8% for the gadolinium doped spinel. Moreover, the total organic compound (TOC) removal was boosted from 17% to 40% when cobalt ferrite was doped with lanthanum. The important boost in catalytic performance of doped samples was explained by a cumulative effect of reduction of size factor and the spinel phase purity as determined by Rietveld refinement of XRD patterns. Additionally, the performance of gadolinium containing catalyst was further improved by modeling and optimization of catalyst dose and hydrogen peroxide concentration, so the CWPO rate constant was enhanced from 1.611 × 10 −1 up to 2.838 × 10 −1 (min −1 ). Graphical Abstract: ga1 Highlights: Co ferrite doped with La, Gd and Dy used as catalyst for CWPO of Rh6G. The smaller ratio grain size/crystallite size improves the catalytic performance. Higher spinel phase purity enhances the catalytic activity. Modeling and optimization of CWPO process almost doubled rate constant.